2004
DOI: 10.1038/sj.eye.6700668
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal gland prolapse in blepharochalasis

Abstract: Blepharochalasis is an uncommon disorder that sometimes requires surgical management in the form of blepharoplasty. We present such a case with an unexpected perioperative finding of lacrimal gland prolapse.Case report

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…They had similar findings in that two-thirds of these patients had focal lymphocytic change and the other third had no pathological changes. 12 Hundal et al 3 published a case report where lacrimal gland prolapse was identified preoperatively in a patient with blepharochalasis. Tissue biopsy of the lacrimal gland performed intraoperatively identified chronic inflammatory infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They had similar findings in that two-thirds of these patients had focal lymphocytic change and the other third had no pathological changes. 12 Hundal et al 3 published a case report where lacrimal gland prolapse was identified preoperatively in a patient with blepharochalasis. Tissue biopsy of the lacrimal gland performed intraoperatively identified chronic inflammatory infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue biopsy of the lacrimal gland performed intraoperatively identified chronic inflammatory infiltration. 3 Xin et al 13 reported histopathological findings in 23 patients with lacrimal gland prolapse and blepharochalasis. Changes identified included inflammatory infiltration, elastic fiber degeneration, marked loosening of the supporting fascia tissue, and an increased level of immunocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroscopically, the prolapsed lacrimal tissue resembles hypertrophied fat, which can lead to an inadvertent lacrimal resection during blepharoplasty, with subsequent aqueous tear deficiency and resultant damage to the surface of the eye. 34,35 MC-MR imaging evaluation of palpebral swelling can alert ophthalmic surgeons to this diagnosis, as was the case in Fig 4, and help avoid inadvertent lacrimal gland resection.…”
Section: Lacrimal Gland Prolapsementioning
confidence: 95%
“…17 The correction of lacrimal gland ptosis has already been described by several authors in the literature. 3,9,[12][13][14][18][19][20][21][22][23][24][25][26][27] However, most of these series found are small and there is no literature review that compiles and synthesizes their results and possible complications.…”
mentioning
confidence: 99%